Social Construction: The Role of Community Empowerment Institutions (LPM) in the Village Fund-Based Development Process (Qualitative Study in Gunung Sari Ilir Village) - Ahmad, Arwani; Ratna, Kusuma Aji; Daryono, Daryono (Jurnal Pemerintahan dan Politik Lokal, 2025)
This study examines the dynamics of challenges, strategies, and institutional implications in realizing participatory development in Gunung Sari Ilir Village, with a particular focus on the role and legitimacy of the Community Empowerment Institution (LPM) as a central actor in local governance. The research explores how structural power relations, administrative capacity, and citizen participation interact to shape the effectiveness and social credibility of participatory institutions. Using a qualitative-descriptive approach supported by thematic and inferential analysis, the study employs in-depth interviews, participatory observation, and document analysis to capture the complex social realities of community participation. The data were analyzed through a combination of thematic coding and interpretive synthesis to identify the patterns of legitimacy construction, governance challenges, and adaptive institutional responses. The findings reveal that participatory development in Gunung Sari Ilir is constrained by persistent elite influence, limited administrative professionalism, and weak transparency mechanisms that collectively undermine trust and inclusiveness. Despite these barriers, local actors employ adaptive strategies such as community consultation, leadership strengthening, and information openness to enhance institutional legitimacy and promote collaborative development practices. The study concludes that participatory governance is not a linear process but an evolving negotiation between institutional structures and social actors, where legitimacy is continuously constructed through transparency, accountability, and communicative engagement. This research contributes to the broader understanding of local governance by highlighting the interdependence between institutional capacity, social trust, and participatory sustainability.